Zinc-Doped Copper Oxide Nanocomposites Inhibit the Growth of Pancreatic Cancer by Inducing Autophagy Through AMPK/mTOR Pathway - Li, Xiao; Xu, Huanli; Li, Cong; Qiao, Gan; Farooqi, Ammad Ahmad; Gedanken, Aharon; Liu, Xiaohui; Lin, Xiukun (Frontiers in Pharmacology, 2019)
Zinc doped copper oxide nanocomposites (Zn-CuO NPs) is a novel doped metal nanomaterial synthesized by our group using the sonochemical method. Our previous studies have shown that Zn-CuO NPs could inhibit cancer cell proliferation by inducing apoptosis via ROS-mediated pathway. In the present study, we studied the anticancer effect of Zn-CuO NPs on human pancreatic cancer cells. MTS assay revealed that Zn-CuO NPs was able to inhibit cancer cell growth. TEM, flow cytometry and fluorescence microscope analysis showed that Zn-CuO NPs induced autophagy significantly; the number of autophagosomes increased obviously in cells treated with Zn-CuO NPs. Western blot analysis revealed that treatment with the NPs resulted in activation of AMPK/mTOR pathway in both AsPC-1 and MIA Paca-2 cells in dose dependent manners. Moreover, in the presence of AMPK activator AMPKinone, the protein level of p-AMPK, p-ULK1, Beclin-1 and LC3-II/LC3-I increased, while the protein expression of p-AMPK, p-ULK1, Beclin-1 and LC3-II/LC3-I decreased in the presence of AMPK inhibitor Compound C. In vivo study using xenograft mice revealed that Zn-CuO NPs significantly inhibited tumor growth with low toxicity. Our study confirms that Zn-CuO NPs inhibit the tumor growth both in vitro and in vivo for pancreatic cancer. AMPK/mTOR pathway plays an important role in the NPs induced inhibition of tumor growth.